Characteristics of Causes and Analysis of Factors Affecting Mental and Psychological Health of a Child - Zdanevych, Larysa; Krutii, Katerina (Pedagogical Discourse, 2017)
The article reveals the actual problem of determining the level of mental and psychological health of preschoolers and schoolchildren. It is noted that children whose status can be described as marginal in relation to norms and qualify as «not mentally ill, but psychologically no longer healthy» continue to remain out of sight and positive intervention nowadays. It is mentioned that traditional psychiatric service involves work only with the contingent having fixed medical «status» – diagnosis, account form, and the like. Outside the attention of doctors-psychiatrists remain significant number of children and adolescents with borderline states, which complicate the adaptation of children in the society, their ability to fulfil the requirements of the educational program. The definitions of «mental health», «psychological health» have been characterized, the content of the concepts has been defined and the author’s approach to the delimitation of these concepts and their criteria has been proposed. It has been found out that mental health is the maximum degree of personality display at the adequate level of its adaptation (lack of disadaptation) to the environment and the absence of mental disorders. The attention is focused on the main criteria of mental health. The views of scientists on the definition of the term «psychological health» have been analyzed. It is determined that the term «psychological health» refers to the person as a whole, to manifestations of the human spirit, which allows separating the psychological aspect from the medical, sociological, and philosophical. It is psychological health that makes the person self-sufficient. The criteria for psychological health have been singled out and characterized. The factors influencing the child’s psychological health have been characterized and analyzed. Most of these factors are of socio-psychological, socio-cultural and socio-economic character. The conclusion is made that psychological health is undoubtedly related to mental health, the latter forms the basis for the psychological health. In other words, mental health is a specific concept for understanding psychological health. Undoubtedly, the best preventive measure of disadaptation is the preservation of the mental and psychological health of children, good relations between parents and children, understanding by the adults inner world of their children, their problems and experiences, ability to put themselves in the place of their children.